Peran Strategis Supreme Audit Institution dalam Mengawal SDGs: Sebuah Tinjauan Literatur Sistematis - Maesya Putrina Sitepu (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The approaching 2030 deadline for achieving the Sustainable Development Goals (SDGs) requires stronger sustainability accountability that goes beyond administrative compliance toward substantive impact. However, sustainability reporting practices remain vulnerable to greenwashing and face challenges in ensuring the validity of non-financial data, thereby necessitating the role of Supreme Audit Institutions (SAIs) in safeguarding the credibility of development reporting. This study aims to examine how the role of SAIs is conceptualized within the sustainability accountability discourse and their contribution to supporting SDG achievement. It employs an interpretive Systematic Literature Review (SLR) approach based on the PRISMA 2020 protocol, analyzing 25 reputable journal articles published between 2016 and 2026 using thematic analysis. The findings identify five key dimensions of SAIs’ roles: governance, data quality assurance, digital audit, regulatory, and human capital capacity. These dimensions reflect a fundamental shift in public sector auditing from administrative compliance toward strategic accountability oriented to the credibility of sustainability reporting. The findings are interpreted through Agency Theory, Legitimacy Theory, and Institutional Theory to explain the positioning of SAIs, including BPK RI, within the global sustainability audit landscape. This study provides practical insights for BPK RI in developing an audit roadmap that supports more substantive SDG outcomes and contributes to the public sector auditing literature.